Extract Sunscreen Activity Test Ethanol leaves of Matoa (Pometia pinnata) in-Vitro - Ayu Rismiasih; Adhisty Kharisma Justicia (Jurnal Komunitas Farmasi Nasional, 2022)
Research has been carried out entitled “Extract Sunscreen Activity Test Ethanol leaves of Matoa (Pometia pinnata) in-Vitro”. Matoa leaves contain flavonoid compounds. this study aims to find out whether ethanol extract matoa leaves (pometia pinnata) have sunscreen activity. The sunscreen activity test is done in vitro using the spectrophotometer UV-Vis with Mansur's equation. Ethanol extract matoa leaves were core liquid with a concentration of 1000 ppm, then dilution is done with concentrations of 200 ppm, 400 ppm, 600 ppm, and 800 ppm. Research result shows that ethanol extract matoa leaves have a value of SPF tall one so they can potentially as a sunblock. SPF value obtained at each concentration of 200 ppm, 400 ppm, 600 ppm, and 800 ppm in a row is 8,15; 18,19; 27,97; and 29,27, where ethanol extract matoa leaves at each of 400 ppm, 600 ppm, and 800 ppm have the best SPF value with ultra protection